2012
DOI: 10.1007/s11060-012-0816-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurological outcome of childhood brain tumor survivors

Abstract: We assessed neurological and neurocognitive outcome in childhood brain tumor survivors. Altogether, 75 out of 80 brain tumor survivors diagnosed below 17 years between 1983 and 1997; and treated in Tampere University Hospital, Finland, were invited to participate in this population-based cross-sectional study. Fifty-two (69%) participated [mean age 14.2 (3.8-28.7) years, mean follow-up 7.5 (1.5-15.1) years]. Neurological status was abnormal in 69% cases. All were ambulatory, but only 50% showed normal motor fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 23 publications
0
39
0
3
Order By: Relevance
“…Table 3 presents the multivariable analysis for measures of sodium derangement individually adjusted for patient factors previously associated with poor outcome (age, obstructive hydrocephalus, tumor location, and malignant histology). 1,8,9,11,12,14,15,[21][22][23]29 Rapid declines in serum sodium > 15 mEq/L within 24 hours, nadir sodium concentration, duration of hyponatremia, and number of episodes of hyponatremia all remained independently associated with increased odds of poor outcome.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 3 presents the multivariable analysis for measures of sodium derangement individually adjusted for patient factors previously associated with poor outcome (age, obstructive hydrocephalus, tumor location, and malignant histology). 1,8,9,11,12,14,15,[21][22][23]29 Rapid declines in serum sodium > 15 mEq/L within 24 hours, nadir sodium concentration, duration of hyponatremia, and number of episodes of hyponatremia all remained independently associated with increased odds of poor outcome.…”
Section: Resultsmentioning
confidence: 99%
“…1,7,17,21,22,27,32 Macedoni-Luksic et al reported 62% of children with brain tumors had at least 1 neurological impairment, with 22% moderately disabled and 2% severely disabled more than 3 years after treatment. 17 Sønderkaer et al reported 69% of patients with brain tumors had a neurological deficit approximately 10 years from treatment, and using the Bloom's score, which closely mirrors aspects of the PCPC score, they estimated 23% had moderate disability and 2% had severe disability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations